Using Human-Induced Pluripotent Stem Cells to Model Monogenic Metabolic Disorders of the Liver - Ordonez, Maria Paulina; Goldstein, Lawrence S.B. (Seminars in Liver Disease, 2012)
A crucial problem in liver disease biology and a major obstacle to the development of new therapies is the inability to conduct mechanistic studies of live human hepatocytes. Liver tissue from patients is difficult to obtain and only reveals the disease aftermath, while animal models lack the significant genetic diversity of humans. Monogenic metabolic disorders of the liver are an ideal platform to explore the complex gene–environment interactions and the role of genetic variation in the onset and progression of liver disease. Human induced pluripotent stem cell (hIPSC) technology provides an unprecedented opportunity to generate live cellular models of disease for therapeutic candidate discovery and cell replacement therapy. In this review, we discuss the potential of hIPSC to increase our understanding of human disease with a focus on the current efforts to model metabolic diseases of the liver and to generate suitable populations of human hepatocytes for cell transplantation.
Keywords: human-induced pluripotent stem cells; hepatocyte differentiation; disease modeling; inherited liver metabolic disorders; cell transplantation